Corporate insolvency - Totty, Peter; Crystal, Michael (London ; New York : McGraw-Hill, 1982)
This book concentrates on those aspects of corporate insolvency which are likely to be encountered in practice and does not attempt to provide a detailed description of all the complex procedural aspects of this subject which are more appropriately to be found in standard practitioners works on company law. The book attempts to consider receivership and liquidation together for the most part.
Includes bibliographical references and index.
ne 22/01/2019, ijb 19/03/2019
Loans
Keywords: Bankruptcy; Corporation law; Great Britain